An unusual cause of paraesthesia in a neo-adjuvant gastro-oesophageal cancer. Issue 8 (22nd August 2019) - Derby, Sarah; Graham, Janet; McIntosh, David
Abstract : There is ongoing debate about the best neo-adjuvant strategy for localised resectable oesophageal cancer, however chemotherapy is often employed. Both oesophageal cancer and cisplatin carry an increased risk of thrombosis. Here, we look at an unusual finding in a previously fit woman who presented following neo-adjuvant chemotherapy for resectable oesophageal cancer with increasing difficulty in walking and lower limb paraesthesia. This case looks particularly at the diagnostic challenge and concerns raised in a patient undergoing radical treatment as well as the challenge of complications secondary to treatment with chemotherapy. Willingness to reassess and revisit is a vital part of the diagnostic process. Vascular complications of a disease can be notorious to diagnose and, as in this case can mimic arguably more logical diagnoses. Cancer care provides the unique challenge of investigating unusual presentations related both to disease and treatment.